The ire of Iron Claw - Hamilton, K. R. (Kersten R.) (Hamilton, K. R. (Kersten R.) Gadgets and gears, 2015)
"The daring and loyal dachshund Noodles, the boy inventor Wally Kennewickett, and his scientific genius family and staff of automatons join forces with Nikola Tesla to defeat sky pirates, cross Europe in a giant mechanical spider, and defy the evil Mesmers"--Provided by publisher.